Social Entrepreneurship : building impact step by step - Chahine, Teresa (New York, NY : Routledge, 2023)
"Social Entrepreneurship provides a twelve-step framework for building impactful ventures in new and existing organizations. The book summarizes the basic steps and tools needed to understand the challenge you are tackling, develop potential solutions, build a business model, measure, and grow your impact. This fully updated 2nd edition builds on the concepts and tools introduced previously, broadening the scope to those working or preparing to work in organizations globally. Concepts addressed include intrapreneurship and, for the first time, extrapreneurship, which considers innovating across organizations to achieve collective impact. Featuring international case studies, innovative diary entries and interviews with leaders in the field, this comprehensive guide spans multiple sectors, including health, the environment, education, agriculture, commerce, finance, and retail. Exercises, summaries and key learning points help to aid and cement learning. A widely regarded and valuable text, Social Entrepreneurship should be core reading for advanced undergraduate and postgraduate students studying Entrepreneurship and Social Entrepreneurship. The book's applied 12-step approach, and those in Executive Education, as well as professionals and entrepreneurs looking to equip themselves with the tools needed to succeed. Online resources include chapter-by-chapter PowerPoint slides and a test bank"--
Earlier edition published as: Introduction to social entrepreneurship.
Keywords: Social entrepreneurship